Rancang Bangun Sistem Informasi Perizinan Penyelenggaraan Sekolah Swasta Berbasis Web Pada Dinas Pendidikan Provinsi Jawa Timur - Setiajie, Aditya Putra; Nurcahyawati, Vivine; Wahyuningtyas, Nunuk (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Education Office of East Java Province is one of the government agencies that provide educational services to the community such as school establishment permits, extension of school establishment permits, management of student transfers, and other educational services. The process of arranging establishment permits, extensions, amendments and closure of education or school units by bringing and requirements documents that must be submitted to Education Office of East Java Province. The time needed for one management can take up to one month The waterfall method is used to provide solutions to problems that exist in the Education Office of East Java Province. This method implies a systematic and sequential approach to software development. Software development starts from the specifications of user needs and continues through the stages of planning, modeling, construction, and deployment, which ends with ongoing support for the software produced. With the existence of a web-based private school licensing information system that can shorten the management time of permits, applicants can register directly through the media website and also upload licensing requirements without having to queue at Education Office of East Java Province